(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Hepatitis B are endemic in tropical and sub-Saharan Africa. The Epidemiological Study of Hepatitis B infection among pregnant women in Gombe, Gombe State, Nigeria was carried out on 1521 patients reporting for their first antenatal clinic in hospitals and clinics, in Gombe, Gombe State. The serum/plasma test for hepatitis B using strip was done with their socio-demographic parameters were determined. Most of the participants were between 21-30years (56.34), while those with secondary education (49.85%) and housewives (99.41%). The prevalence of hepatitis B was 1.51% with the highest prevalence among age group 21-30years with (63.57%), while the highest prevalence was among those in second trimester (2.29%) and those in primigravidea (3.70%). Those that had secondary education had the highest prevalence of hepatitis B (1.85%), while the business-oriented women had the highest prevalence of hepatitis B (7.84%), and the highest prevalence of hepatitis B was among the married (1.51%). The prevalence of hepatitis B was statistically significant with age group. We advise that measures encouraging personal and environmental hygiene should be encouraged as well as blood screening for hepatitis B should be done.